2015
DOI: 10.3389/fmicb.2015.00237
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ser/Thr/Tyr phosphoproteomics between two mycobacterial species: the fast growing Mycobacterium smegmatis and the slow growing Mycobacterium bovis BCG

Abstract: Ser/Thr/Tyr protein phosphorylation plays a critical role in regulating mycobacterial growth and development. Understanding the mechanistic link between protein phosphorylation signaling network and mycobacterial growth rate requires a global view of the phosphorylation events taking place at a given time under defined conditions. In the present study we employed a phosphopeptide enrichment and high throughput mass spectrometry-based strategy to investigate and qualitatively compare the phosphoproteome of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…8). Our results are in agreement with an independent study wherein RodA was identified to be phosphorylated at Thr-463 in Mycobacterium bovis BCG (71). In vitro kinase assays with purified STPKs showed that PknB and PknH are the most likely STPKs to mediate phosphorylation of RodA (Fig.…”
Section: Deciphering the Roles Of Roda And Pbpa In Mycobacteriasupporting
confidence: 93%
“…8). Our results are in agreement with an independent study wherein RodA was identified to be phosphorylated at Thr-463 in Mycobacterium bovis BCG (71). In vitro kinase assays with purified STPKs showed that PknB and PknH are the most likely STPKs to mediate phosphorylation of RodA (Fig.…”
Section: Deciphering the Roles Of Roda And Pbpa In Mycobacteriasupporting
confidence: 93%
“…rCTL0511 was incubated with okadaic acid (OA) (17), cyclosporine (CsA), or sodium pyrophosphate (SPP), and phosphatase activity was assayed at 37°C with 25 mM MnCl 2 and pNPP as a substrate. Relative activity was calculated as the percentage of activity remaining in the presence of the inhibitor versus the activity in assay buffer containing DMSO.…”
Section: Figmentioning
confidence: 99%
“…Phosphorylation of protein substrates can lead to direct modulation of protein function or alteration of gene expression on a global level, in the case of activation of transcription factors or signaling pathways (13). In bacteria, Ser, Thr, and Tyr protein phosphorylation, which was once considered to be exclusive to eukaryotes, has gained increasing attention due to its role in major cellular events, including regulation of virulence, stress responses, and differentiation (11,(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…43 Repurposing drugs designed for other indications can also produce new antibiotics or anti-virulence agents, with the added benefit of known safety and pharmacokinetic profiles. 44,45 …”
Section: Introductionmentioning
confidence: 99%